Women With and Against the Mafia: a Case Study of Sicily - Martellozzo, Elena (SIAK-Journal, 2005)
The business of the Mafia is largely by definition the preserve of men; men who have displayed a remarkable talent for cunning, cruelty, murder and mayhem. For the most part, women have remained silent and unseen, or, as most scholars would say, they have remained "invisible". The fact that the Mafia is a secret, criminal monosex male organization is of particular importance when starting from a viewpoint of subjectivity and when listening to those who have experienced the Mafia is a known fact that only men can become part of the Mafia: A man can be affiliated to the Mafia, while a woman can only belong to it, in so far as she belongs to a Mafia man. Thus, it could be argued that the thin line that both separates and distinguishes the affiliation with the Mafia between man and women is the formal ceremony during which each novice,strictly male, has to swear an oath of faithfulness and silence. However, this different way of been associated to the Mafia is merely a formality; a formality that has often led the society to believe that women are extraneous to the Mafia and unaware of the activities of their menfolk. It is the aim of this paper to reject this contention and to prove that this is a naïve and dangerous misconception.